1995
DOI: 10.1038/376672a0
|View full text |Cite
|
Sign up to set email alerts
|

Improving enzyme–electrode contacts by redox modification of cofactors

Abstract: Efficient electron transfer of redox proteins to and from their environment is essential for the use of such proteins in biotechnological applications such as amperometric biosensors and photosynthetic biocatalysts. But most redox enzymes lack pathways that can transport an electron from their embedded redox site to an electrode or a diffusing photoexcited species. Electrical communication between redox proteins and electrode surfaces has been improved by aligning proteins on chemically modified electrodes, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
114
0
12

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 236 publications
(126 citation statements)
references
References 14 publications
0
114
0
12
Order By: Relevance
“…Uma outra maneira de se estabelecer melhor contato elétrico entre o centro redox da enzima e a superfície do eletrodo é por meio do método de reconstituição da enzima. Neste processo, o mediador é ligado diretamente ao centro redox da enzima, sendo a apoenzima (enzima sem o centro redox) posteriormente reconstituída sobre a superfície do eletrodo, de acordo com o esquema mostrado na Figura 8 118,120 . Empregando-se este método foi construído um sensor para glicose 121 , onde o mediador pirroloquinolina quinona (PQQ) foi covalentemente ligado a uma monocamada de cisteamina e, posteriormente, reagido com um derivado amina do FAD, o N(6)-(2-aminoethyl)-FAD.…”
Section: Eletrodos Modificados Com Sam -Análise De Compostos Orgânicosunclassified
“…Uma outra maneira de se estabelecer melhor contato elétrico entre o centro redox da enzima e a superfície do eletrodo é por meio do método de reconstituição da enzima. Neste processo, o mediador é ligado diretamente ao centro redox da enzima, sendo a apoenzima (enzima sem o centro redox) posteriormente reconstituída sobre a superfície do eletrodo, de acordo com o esquema mostrado na Figura 8 118,120 . Empregando-se este método foi construído um sensor para glicose 121 , onde o mediador pirroloquinolina quinona (PQQ) foi covalentemente ligado a uma monocamada de cisteamina e, posteriormente, reagido com um derivado amina do FAD, o N(6)-(2-aminoethyl)-FAD.…”
Section: Eletrodos Modificados Com Sam -Análise De Compostos Orgânicosunclassified
“…Schuhmann 13 used ferrocene modified glucose oxidase, both of them attached to each other via long and flexible spacer chains within conducting polymer films. Katz et al 15,16 reported the preparation of a glucose biosensor by removing FAD (flavine adenine dinucleotide) from GOx and reintroducing the ferrocene-modified FAD again into the GOx. In this way, authors improved the electrical communication between the electrode and the reconstituted enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the sensitivity of the multiplexed bioelectrodes, either a GOx solution is mixed thoroughly with a chitosan/carbon nanotubes one or a LOx layer is sandwiched between two layers of chitosan/carbon nanotubes at pH 7.2. The mixture stands on a thinner Prussian blue layer mediator that has been preliminary electrodeposited on a bare Au electrode (promotes better immobilization [19,[44][45][46]). In such a configuration, the input will be the substrate (glucose, lactate) and the output current (between the working electrode and the counter-electrode) of the sensor can be converted to a voltage through a transimpedance amplifier.…”
Section: Second-generation Glucose-sensing Bioelectrocatalysismentioning
confidence: 99%